Employee attributes, organisational factors, time management tendencies, and employee performance in chartered universities in kenya - Ogeto, Fronica m. (My University, 2013)
The concept of time is as a major topic for organizational and management research. This research investigates the influence of time management tendencies and organizational factors on the relationship between employee attributes and performance. The one-sizefits-all approach to management for ensuring maximum employee performance is no longer an appropriate strategy (Riccucci, 2002). University staff are always under great pressure to conduct research, publish articles, teach classes, advise students and serve on committees. Successfully balancing and juggling all commitments requires an organized approach to both time and task management. This formed the basis for carrying out this study. The main objective of the study was to determine the influence of time management tendencies and organizational factors on the relationship between employee attributes and performance in chartered universities in Kenya. The present study is based on two theories – attention-based theory and the theory of reasoned action. A crosssectional survey of all employees in all chartered universities in Kenya was conducted using a questionnaire on organizational performance, individual attributes, organizational factors and time management tendencies. A sample size of 1365 employees of the universities was randomly selected. Using quantitative and qualitative techniques to analyze data collected. Through linear regression and stepwise multiple regression, the results from the study have demonstrated that there is a relationship between employee attributes of satisfaction, empowerment, motivation, commitment and competence and employee performance as exhibited by effectiveness and efficiency. When the elements are considered individually, the results show that employee satisfaction and employee motivation have a negative relationship on employee performance. The other variables – empowerment, commitment and competence – have a positive relationship on employee performance. The results also show that a significant relationship exists between organizational factors (strategy, structure, leadership and culture) and employee performance. Organizational factors were also found to positively and significantly moderate the relationship between employee attributes and employee performance. In relation to time management behaviors, the research demonstrated that certain time management behaviors have a direct and an indirect effect on performance. Time management tendencies were also found to positively and significantly moderate the relationship between employee attributes and employee performance. Preference-driven variations in the temporal pattern of employees’ activities affect their strategic decision processes and, consequently, organizational performance. This leads to the conclusion that time management tendencies and organizational factors influence the relationship between employee attributes and performance in the workplace. The findings are relevant as they provide vital information to managers, supervisors and employees. Therefore, universities through the human resource departments should consider time management tendencies and organizational factors in determining the employment of its staff, noting that it is potentially beneficial to understand the differences in workplace attitudes and behaviors which affect the use of time so that the "right" mix of individuals may be hired to fit an organization’s situation